2018
DOI: 10.1108/jmtm-06-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated performance measurement framework for lean organizations

Abstract: Purpose The purpose of this paper is to propose an integrated performance measurement framework to measure the effect of lean implementation throughout all functions of an organization. Design/methodology/approach The paper identifies the seven categories representing all organizational functions. These categories have been divided into 26 performance dimensions and key performance indicators (KPIs) for each performance dimension have been identified to measure lean performance. The interrelationship of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 106 publications
0
72
0
2
Order By: Relevance
“…Raffoni et al (2018) explored the potential of performance management systems and indicated that Business Performance Analytics (BPA) can contribute to identifying critical performance variables, potential sources of risk and related interdependencies. Sangwa and Sangwan (2018) developed performance measurement framework for lean organizations and identified the seven categories representing all organizational functions, dividing into 26 performance dimensions and key performance indicators (KPIs) for each performance dimension in the context of lean principles. Trstenjaka and Cosic (2017) researched a process planning changes in Industry 4.0 environment.…”
Section: Theoretical Arguments To Analyse Performance Measurement In mentioning
confidence: 99%
See 1 more Smart Citation
“…Raffoni et al (2018) explored the potential of performance management systems and indicated that Business Performance Analytics (BPA) can contribute to identifying critical performance variables, potential sources of risk and related interdependencies. Sangwa and Sangwan (2018) developed performance measurement framework for lean organizations and identified the seven categories representing all organizational functions, dividing into 26 performance dimensions and key performance indicators (KPIs) for each performance dimension in the context of lean principles. Trstenjaka and Cosic (2017) researched a process planning changes in Industry 4.0 environment.…”
Section: Theoretical Arguments To Analyse Performance Measurement In mentioning
confidence: 99%
“…In relation to the scientific literature review could be stated that different Industry 4.0 clusters have been researched in the context of performance measurement such as Big Data, IoT, analytics digitalization and human -machine interaction (Raffoni et al, 2018;Papadopoulos et al, 2017;Van der Stede, 2016;Schoenherr & Speier-Pero, 2015;Hazen et al, 2014;Waller & Fawcett, 2013). Also it could be noted that the literature is still lacking an understanding of the main changes and developments of performance measurement system in the context of industrial revolution as different studies are fragmented, analyse a separate function of performance measurement (Raffoni et al, 2018;Trstenjaka & Cosic, 2017;Papadopoulos et al, 2017) or are limited to a specific context (Sangwa & Sangwan, 2018). The most commonly used measurement methods were analysed (Table 1) in order to indicate the main functions of performance measurement in business organizations which could allow to research its changes and developments.…”
Section: Theoretical Arguments To Analyse Performance Measurement In mentioning
confidence: 99%
“…Nowadays, LM covers the multiple stages of a product's life cycle, from its development and manufacturing to its delivery [3]; however, LM is also a challenge amid mass production practices, especially as quality products, and customer satisfaction are prioritized, inventory, time to market and manufacturing space, and everything that adds no value to a product is systematically categorized as waste [4]. LM is often discussed with respect to key performance indicators (KPIs) [5,6]. In addition, Kan et al [7] affirm the KPI parameters have an association with LM performance.…”
Section: Introductionmentioning
confidence: 99%
“…performance measures were selected to evaluate SC performance based on the fact that these measures are the most common measures used in the majority of researches and recent in dates e.g. (Chavez et al, 2013;Taj & Morosan, 2011;Nawanir et al, 2016;Arif-Uz-Zaman & Ahsan, 2014;Ruiz-Benítez et al, 2018;Filho et al, 2016;Sharma et al, 2015;Shah & Ganji, 2017;Prajogo et al, 2016;Khanchanapong et al, 2014;Azfar et al, 2014;Dora et al, 2016;Kumar et al, 2015;Afonso & Cabrita, 2015;Droge et al, 2004, Jacobs et al, 2007Machuca et al, 2011;Rosenzweig et al, 2003;Folinas et al, 2014 ;Sangwa & Sangwan, 2018;Arif-Uz-Zaman & Ahsan, 2014;Behrouzi &Wong, 2011;Chavez et al, 2015). From which, the measures were classified into four different performance attributes (cost, time, quality, flexibility), those attributes are highly common in these researches that have discussed lean practice and performance topics.…”
mentioning
confidence: 99%